2019
DOI: 10.1002/pssb.201900173
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Modeling on the Deformation Behavior of Auxetic Tubular Braid Made from Modified Circular Braiding Technique

Abstract: Herein, a theoretical analysis of auxetic tubular braid (ATB) formed with three types of component yarns having different diameter and modulus is presented. A simple theoretical model is developed for predicting the deformation behavior of this structure under uniaxial extension. With its accuracy first validated by the experimental data, the developed model is further corrected based on the real condition and thus becomes capable to characterize the auxetic behavior of the ATB. During the analysis, it is foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 28 publications
(67 reference statements)
0
10
0
Order By: Relevance
“…Different from traditional Helical Auxetic Yarns (HAYs), the core yarn in the BAYs was not completely stretched at the initial state, but had a little bend itself, which was equivalent to a pre-stretched state. Different from the BAYs in Jiang et al 21 and Chen et al 22 the diameter of the BAYs was smaller, which made its application value more extensive. In the process of stretching, the buckling of the core yarn gradually increased, and the rigid yarn gradually tried to change from bending to the stretching state.…”
Section: Resultsmentioning
confidence: 86%
“…Different from traditional Helical Auxetic Yarns (HAYs), the core yarn in the BAYs was not completely stretched at the initial state, but had a little bend itself, which was equivalent to a pre-stretched state. Different from the BAYs in Jiang et al 21 and Chen et al 22 the diameter of the BAYs was smaller, which made its application value more extensive. In the process of stretching, the buckling of the core yarn gradually increased, and the rigid yarn gradually tried to change from bending to the stretching state.…”
Section: Resultsmentioning
confidence: 86%
“…Akin to a HAY, under tensile deformation the radius of the metal helix decreases, and the core deforms into a helical configuration to accommodate the compression (Figure 3c, II-IV). For given wrap and core materials, the main geometric parameter controlling mechanical properties of HAYs is the initial angle α 0 between the helical wire and the cross section of the fiber (wrapping angle), [56][57][58][59] which is given by:…”
Section: D Helical Electrodesmentioning
confidence: 99%
“…Hundreds (if not thousands) of papers have been devoted to matching the values of geometric and/or material parameters of microstructures in such a way as to enable the control of the effective Poisson's ratio values ν H in the full range of its permissible values, that is, −1 ≤ ν H ≤ 1 and −1 ≤ ν H ≤ 0.5 for 2D and 3D elastic, isotropic bodies, respectively—see for example, the selected and the most current studies. [ 24–60 ] It is worth emphasizing that a clear and simple proving of the earlier permissible ranges of Poisson's ratio for isotropic material was disclosed by Wojciechowski [ 24 ] published almost 20 years ago. More than 30 years ago, the same author showed that simple hexagonal units (hard cyclic hexamers) spontaneously form an auxetic isotropic crystal in two dimensions (see the study by Wojciechowski [ 25 ] ).…”
Section: Introductionmentioning
confidence: 99%